Donor Commitments and Disbursements for Sexual and Reproductive Health Aid in Kenya, Tanzania, Uganda and Zambia - Kibira, Denis; Asiimwe, Cornelia; Muwonge, Moses; van den Ham, Hendrika A.; Reed, Tim; Leufkens, Hubert G.; Mantel-Teeuwisse, Aukje K. (Frontiers in Public Health, 2021)
Background Sexual and Reproductive Health and Rights (SRHR) investments are critical to people’s wellbeing. However, despite the demonstrated returns on investments, underfunding of SRHR still persists. The objective of this study was to characterize donor commitments and disbursements to SRH aid in four sub-Saharan countries of Kenya, Tanzania, Uganda and Zambia and to compare trends in donor aids with SRH outcome and impact indicators for each of these countries. Methods The study is a secondary analysis of data from the Organization for Economic Co-operation and Development’s Assistance creditor reporting system and SRH indicator data from the Global Health Observatory and country demographic health surveys for a 16-year period (2002-2017). We downloaded and compared commitments to disbursements of all donors for population policies, programs and reproductive health for the four African countries. SRH indicators were stratified into health facility level process/outcome indicators (modern contraceptive prevalence rate, unmet need for family planning, antenatal care coverage and skilled birth attendance) and health impact level indicators (maternal mortality ratio, newborn mortality rate, infant mortality rate and under 5 mortality rate). Results Donor commitments for SRH aid grew on average by 20% while disbursements grew by 21% annually between 2002 and 2017. The overall disbursement rate was 93%. Development Assistance Cooperation (DAC) countries donated the largest proportion (79%) of aid. Kenya took 33% of total aid, followed by Tanzania 26%, Uganda 23% and then Zambia (18%). There was improvement in all SRH outcome and impact indicators, but not enough to meet targets. Conclusion Donor aid to SRH grew over time and in the same period indicators improved, but improvement remained slow. Unpredictability and insufficiency of aid may be disruptive to recipient country planning. Donors and low- and middle-income countries should increase funding in order to meet global SRHR targets.